Menggali Potensi Desa: Pemanfaatan Pangan Lokal dan Edukasi Sanitasi Sehat untuk Generasi Bebas Stunting di Desa Sinagar - Wayunah, Wayunah; Zustika, Diana Sri; Ramadhan, Fauzan Sebastian; Sukma, Mentari Nurul; Nurhasanah, Lutfiah; Rahmatunnisa, Rahmatunnisa (Yayasan Inspirasi El Burhani, 2025)
Introduction: Stunting is a major public health problem caused by chronic malnutrition and recurrent infections, resulting in impaired physical growth and cognitive development in children. Sinagar Village has a relatively high prevalence of stunting. Objective: This study aimed to evaluate the effectiveness of the program “Local Food Utilization and Healthy Sanitation Education for Stunting Prevention” in improving community knowledge regarding balanced nutrition, the use of local food, and healthy sanitation practices. Method: The education program was conducted on July 29, 2025, at the Sinagar Village Hall using an educative-participatory and community-based approach. Forty-five participants (pregnant women, breastfeeding mothers, mothers of toddlers, and community health cadres) took part in pre- and post-tests. Data were analyzed using Microsoft Excel to compare mean scores before and after the intervention. Result: The average score from 84.44 in the pre-test to 85.28 in the post-test. Participants demonstrated improved understanding of stunting, the importance of balanced nutrition, exclusive breastfeeding, immunization, and healthy sanitation practices. The program also included the distribution of nutritious milk and fruits, providing additional nutritional intake for target groups. Conclusion: The local food and healthy sanitation education program was effective in enhancing community knowledge for stunting prevention. Continued educational interventions are recommended to promote sustainable behavioral changes that support optimal child growth and health in rural communities.